Obstructive sleep apnea syndrome of unusual cause - Clinical case - Ramos, Nadia Hassamo (2012)
Introduction: The authors describe a clinic case of mild ostructive sleep apnea syndrome, whose study has revealed a right parapharyngeal neoformation at the level of the styloid apophysis, adjacent to the skull base.Material and Methods: 58 year old female patient with with a mild obstructive sleep apnea syndrome diagnosis. The patient had been submitted to uvulopalatoplasty in 2008 without clinical resolution. Structurally the patient presented a classe I modified Friedman’s anatomic classification for Obstructive Sleep Apnea Syndrome, with a type 1 Angle’s class and body mass index of 24. The endoscopic study of the upper airway has not revealed morphological aspects to point out. Sequential diagnostic exams were requested to evaluate possible anomalies of the upper airways.Results: Imaging studies revealed the existence of a expansive lesion centered to the right parapharyngeal area, with oval configuration, and an estimated volume of 20 cm3, conditioning medial deviation of the oropharynx. Elective surgery was performed. The histology was compatible with pleomorphic adenoma of a minor salivary gland.Conclusion: The obstructive sleep apnea syndrome results from structural changes of the upper airway. The determination of the obstructive level is corner stone for decision about treatment planning of this entity. This case represents an unusual and rare etiology that nonetheless fulfils the required criteria for obstructive sleep apnea syndrome to occur, simply because of its location.